2011
DOI: 10.1242/jcs.084657
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potential depolarization decreases the stiffness of vascular endothelial cells

Abstract: The stiffness of vascular endothelial cells is crucial to mechanically withstand blood flow and, at the same time, to control deformation-dependent nitric oxide release. However, the regulation of mechanical stiffness is not yet understood. There is evidence that a possible regulator is the electrical plasma membrane potential difference. Using a novel technique that combines fluorescence-based membrane potential recordings with atomic force microscopy (AFM)-based stiffness measurements, the present study show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 66 publications
10
71
0
1
Order By: Relevance
“…We also found that Na V 1.5 function in cancer cells enhanced Src kinase activity and Y421 cortactin phosphorylation, which could contribute to the acquisition of an aggressive phenotype. Although the mechanism has not yet been elucidated, this could be in line with the observation that membrane depolarisation regulates the actin polymerisation:actin depolymerisation ratio and thus, the F-actin network directly under the plasmalemma (Callies et al, 2011). This effect on actin polymerisation could also be dependent on the interaction of actin with NHE-1 through the association with actin-binding proteins of the ERM (ezrin, radixin and moesin) family (Baumgartner et al, 2004;Cardone et al, 2005).…”
Section: Resultssupporting
confidence: 56%
“…We also found that Na V 1.5 function in cancer cells enhanced Src kinase activity and Y421 cortactin phosphorylation, which could contribute to the acquisition of an aggressive phenotype. Although the mechanism has not yet been elucidated, this could be in line with the observation that membrane depolarisation regulates the actin polymerisation:actin depolymerisation ratio and thus, the F-actin network directly under the plasmalemma (Callies et al, 2011). This effect on actin polymerisation could also be dependent on the interaction of actin with NHE-1 through the association with actin-binding proteins of the ERM (ezrin, radixin and moesin) family (Baumgartner et al, 2004;Cardone et al, 2005).…”
Section: Resultssupporting
confidence: 56%
“…When QTc interval is prolonged, it may become a risk factor for ventricular tachyarrhythmias and sudden death. This condition can arise as a genetic syndrome, or may be as a side effect of certain medications, but, an unusually short QTc can be seen in severe hypercalcemia (29,30,31,32). In this study, all the tested doses brought about an increase in QT and QTc interval.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of membrane potential in white blood cells vary from -45 to -86mV [19]. These negatively charged cells are presumably subject to electrostatic repulsion with respect to the negatively charged glycocalyx (electrical potential unknown) and the endothelial cell with trans membrane potential of -80mV, when polarized at extracellular potassium ion (K + ) concentration of 4mM [20]. This could explain, at least in part, the modulation of immobilization of leukocytes at the endothelial surface [21].…”
Section: Electrophysiological Aspectsmentioning
confidence: 99%